Blow up at Infinite Time of Solutions for a Plate Equation with Delay Term - Pişkin, Erhan; Yüksekkaya, Hazal (Journal of Nepal Mathematical Society, 2024)
In this article, we investigate the viscoelastic plate equation with both delay and source terms. Initially, we give the local-global existence results. Later, we establish the blow-up results at infinite time by utilizing the energy method when E (0) < 0 under suitable conditions. Delays effect generally seems in many practical problems for instance medicine, biological, chemical, physical, thermal, economic phenomena, electrical engineering systems and mechanical applications.